Do Remittances Affect Foreign Direct Investment? A Comprehensive Analysis of BRICS-T Nations - Abdioglu, Nida; Aytekin, Sinan (Panoeconomicus, 2025)
This study investigates the impact of remittances and the International Property Rights Index on foreign direct investment (FDI) in BRICS-T countries during the period from 2007 to 2023. FDI is employed as the dependent variable, while the independent variables comprise remittances, trade openness, financial development, government consumption, and the International Property Rights Index. The long-term results indicate that remittances exert a positive influence on FDI over the long run. However, contrary to expectations, the International Property Rights Index demonstrates a negative long-term effect on FDI. Although sound governance and strong institutional frameworks are generally considered essential for attracting FDI and strengthening the relationship between FDI and remittances, this pattern does not appear to apply to BRICS-T countries. In the short run, by contrast, the International Property Rights Index has a positive effect on FDI, implying that high governance quality tends to attract FDI over shorter time horizons. JEL: C33, F21, F24